Analgesic and Anti-Inflammatory constituents of annickia polycarpa stem and root barks and clausena anisata root. - Kumatia, Emmanuel Kofi (2017)
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in the Department of Pharmacognosy faculty of Pharmacy and Pharmaceutical Sciences College of Health Sciences,